PENGARUH FINANCIAL KNOWLEDGE, FINANCIAL BEHAVIOUR DAN FINANCIAL ATTITUDE TERHADAP FINANCIAL LITERACY PADA MAHASISWA AKUNTANSI KOTA BATAM - Simaremare, Grace Stella; Argo Putra Prima, S.E., M.Ak. (SCIENTIA JOURNAL, 2024)
In the current era of globalization, economic development is rapidly advancing, making it increasingly complex and dynamic. Consequently, financial literacy has become an essential skill that every individual must possess. The aim of this research is to analyze the influence of financial knowledge, financial behavior, and financial attitude on the financial literacy of accounting students in Batam City. This research is quantitative, utilizing primary data obtained from questionnaires distributed to respondents. The population in this study consists of accounting students in Batam City. The sample was selected using a probability sampling method with a simple random sampling technique, employing the Slovin formula for 100 respondents. The analysis technique used is multiple linear regression. The results of this research indicate that all the variables tested have met the assumptions of data quality testing, classical assumption testing, and hypothesis testing. Based on partial test results, it is found that financial knowledge and financial attitude influence financial literacy, whereas financial behavior does not affect financial literacy. According to the F test, the independent variables X1, X2, and X3 simultaneously have a positive and significant effect on the dependent variable Y.